A Randomized, Controlled Trial of Lottery-Based Financial Incentives to Increase Physical Activity Among Overweight and Obese Adults. Issue 7 (September 2018) - Patel, Mitesh S.; Volpp, Kevin G.; Rosin, Roy; Bellamy, Scarlett L.; Small, Dylan S.; Heuer, Jack; Sproat, Susan; Hyson, Chris; Haff, Nancy; Lee, Samantha M.; Wesby, Lisa; Hoffer, Karen; et al.
Purpose: To evaluate the effect of lottery-based financial incentives in increasing physical activity. Design: Randomized, controlled trial. Setting: University of Pennsylvania Employees. Participants: A total of 209 adults with body mass index ≥27. Interventions: All participants used smartphones to track activity, were given a goal of 7000 steps per day, and received daily feedback on performance for 26 weeks. Participants randomly assigned to 1 of the 3 intervention arms received a financial incentive for 13 weeks and then were followed for 13 weeks without incentives. Daily lottery incentives were designed as a "higher frequency, smaller reward" (1 in 4 chance of winning $5), "jackpot" (1 in 400 chance of winning $500), or "combined lottery" (18% chance of $5 and 1% chance of $50). Measures: Mean proportion of participant days step goals were achieved. Analysis: Multivariate regression. Results: During the intervention, the unadjusted mean proportion of participant days that goal was achieved was 0.26 in the control arm, 0.32 in the higher frequency, smaller reward lottery arm, 0.29 in the jackpot arm, and 0.38 in the combined lottery arm. In adjusted models, only the combined lottery arm was significantly greater than control ( P = .01). The jackpot arm had a significant decline of 0.13 ( P < .001) compared to control. There were no significant differences during follow-up. Conclusions: Combined lottery incentives were most effective in increasing physical activity.